The Relationship Between Breastfeeding Position and the Occurrence of Regurgitation In Infants Aged 0-6 Months - AISYAH, FITRIA; Wiqodatul Ummah; Eti Kuswandari; Mufida Annisa Rahmawati; Novi Budi Ningrum (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
One of the problems in the breastfeeding process is regurgitation. Efforts to prevent regurgitation include training in the proper breastfeeding technique. Hold the baby upright so that the air swallowed while sucking can be released. This research analyzes the relationship between breastfeeding position and the occurrence of regurgitation in infants aged 0-6 months in Songgokerto village, Batu city. This study is designed as quantitative research with a cross-sectional approach and uses a post-test only study. Therefore, all mothers with children aged 0-6 months in the Songgokerto sub-district became respondents in this study. The sample size in this study was 30 mothers who have infants aged 0-6 months who experience regurgitation. Univariate data analysis and bivariate analysis with anova test and linear regression test analysis. Analysis result of t count > t table, which is -2.918 > -2.056. This means that there is a significant relationship between Breastfeeding Position and the Occurrence of Regurgitation. The statistical analysis result shows that F count > F table, which is 33.305 > 2.975. This indicates a significant relationship between the variable Breastfeeding Technique (X) and Occurrence of Regurgitation (Y). The analysis result of the R-squared value for variable X (Breastfeeding Position) is 0.794, meaning that the breastfeeding position affects the occurrence of regurgitation by 79.4%, while the remaining 20.6% is influenced by other factors not studied. The significant relationship between breastfeeding position and the occurrence of regurgitation.